In‐Situ Photoelectron Spectroscopy Study on the Air Degradation of PEDOT:PSS in Terms of Electrical and Thermoelectric Properties. (16th September 2020) - Yun, Dong‐Jin; Jung, Jaemin; Sung, Young Mo; Ra, Hyemin; Kim, Jung‐Min; Chung, JaeGwan; Kim, Se Yun; Kim, Yong‐Su; Heo, Sung; Kim, Ki‐Hong; Jeong, Yong Jin; Jang, Jaeyoung
Abstract: Despite excellent electrical and mechanical properties, practical application of poly(3, 4‐ethylenedioxythiophene) polymerized with poly(4‐styrenesulfonate) (PEDOT:PSS) face the challenge of ensuring air stability in electronic industry. Here, degradation mechanism of PEDOT:PSS‐based films in air is clearly demonstrated through X‐ray/ultraviolet photoelectron spectroscopy (XPS/UPS) and its depth‐profiling technique. As the duration of air‐exposure increases, the PEDOT:PSS‐based films alter molecular structures with the formation of SO x bond in PEDOT and CN x bond growth, changing ratios of insulating part (PSS −, PSSH, oxidized PEDOT) to conducting part and deteriorating their electrical conductivities. These transition behaviors are similar in all PEDOT:PSS‐based films regardless of additives such as dopant or multi‐walled carbon nanotube. Additionally, methanol treatment to various PEDOT:PSS‐based films for inducing conformational change between PEDOT and PSS molecules, partly restore the electrical properties of the denatured PEDOT:PSS films. Finally, thermoelectric properties of the PEDOT:PSS‐based films are characterized by investigating the effects of air‐aging and methanol treatment on electrical conductivities, Seebeck coefficients, and power factors. To sum up, this study provides a useful guideline for establishing a strategy to ensure air stability of PEDOT:PSS‐based films by clarifying the degradation mechanism and property recovery methods. Abstract : Environmental stability of PEDOT:PSS is a critical issue for long‐term electrical devices despite their excellent electrical and mechanical properties. Here, degradation mechanism of PEDOT:PSS‐based films is elucidated using in situ photoelectron spectroscopy. Also, simple solvent treatment induces conformational change in PEDOT and PSS, thus good restoration process in terms of electrical and thermoelectrical properties is suggested.